ANALYSIS OF FACTORS DETERMINING THE LEVEL OF JOB SATISFACTION OF PRIVATE COLLEGE LECTURERS IN BANJARMASIN - Arief Noviarakhman Zagladi (Paedagogia: Jurnal Pendidikan, 2022)
ABSTRACT Job satisfaction is a factor that really needs to be considered in various work organizations, including educational organizations, because job satisfaction has been shown to have many influences on various organizational outputs, especially on work performance. This study aims to determine the level of job satisfaction of private college lecturers and which factors have the greatest role in shaping lecturers’ job satisfaction in Banjarmasin City, South Kalimantan. Respondents in this study were 314 permanent lecturers in various private college that still active in Banjarmasin City. Job satisfaction was measured by 5 indicators, each described by a few items. Data analysed using Spearman’s Correlation to determine the correlation between every indicator to it’s total variable. The results of the study found that the most satisfying factor according to the lecturers was the work environment, while the factor that had the biggest role in shaping job satisfaction was workplace guidance, especially the role of leadership in directing and providing input to lecturers. It is hoped that through this research, lecturers' job satisfaction can be maintained and have a positive impact on various other organizational outputs.